Percepção dos agentes envolvidos na logística urbana em BeloHorizonte: um estudo exploratório - Gustavo Fonseca de Oliveira (2015)
The urban freight distribution is vital for a competitive market. However, the problems from this activity deteriorate the life quality in cities. To reduce such impacts, solutions should be investigated and implemented considering the different perspectives and objectives of the key stakeholders (carriers, retailers, population and administrators), so that distribution would be efficient and economically feasible. This study analyzed the preferences and perceptions of those involved in city logistics practices, in the municipality of Belo Horizonte. To achieve this objective, it was used a survey to identify practices that best fit the analyzed reality. For the population, the cargo vehicles contribute for the worsening of the traffic conditions but are not the main cause of the problem and are recognized as important to society. Carriers were willing to participate in certain practices and even pay to participate, since the time that is lost in traffic and in the search for places to load and unload cargo directly influences the transportation cost. The retailers did not show similar patterns to the carriers, not considering the practices effective and neither willing to participate in programs to improve the urban distribution. Besides not consider the measures effectives, some kind of payment to participate in the programs is also not well accepted, since they do not understand some reduction in costs by the optimization, only increase. Public administrators recognize that the investment focus is mainly for passengers transport, but efforts are being made to change this situation, treating the cargo transport with its due importance, established by the law. It is also recognized the need to design and implement programs together with those directly involved, transporters and retailers.